Survival analysis of an orthodontic bracket bond subjected to cyclic tensile and shear forces - Ameerah Y Mansour; Mohamed Bamashmous (Wolters Kluwer Medknow Publications, 2018)
OBJECTIVES: The objective of this study was to evaluate the use of survival analysis in cyclic fatigue testing in orthodontic bracket bonding. MATERIALS AND METHODS: We used 100 extracted bovine lower incisors (50 orthodontic brackets and 50 eyelet brackets). Each set of brackets was further divided by etching technique (25 total-etch and 25 self-etch). Cyclic fatigue testing was performed at a crosshead speed of 2 mm/min using an up-and-down method. Kaplan-Meier survival data analyses and Cox regression analyses were performed. RESULTS: Survival analysis proved to be a simple methodology and revealed that the etching technique was not a statistically significant predictor for survival of orthodontic bracket bonding with either tensile or shear cyclic forces at P > 0.05. In tensile cyclic loading, high mechanical loading after controlling for the etching technique is a statistically significant predictor for lower survival of the orthodontic bracket bond at P < 0.001. CONCLUSIONS: Both etching techniques (total-etch and self-etch) are equally efficient in bonding orthodontic brackets. High mechanical loading is an important predictor of bond failure when applying tensile cyclic forces. Finally, survival analysis is a simpler alternative method to analyze orthodontic bracket bonding subjected to cyclic tensile and shear forces and gives similar results to other complicated methods.